Polskie dyskursy o (i)migracji po 1989 roku. Fazy, charakterystyki, style – wybrane aspekty - SMYKAŁA, MARTA (Stylistyka, 2024)
Should 2015 be considered the year of the birth of (im)migration discourse in Poland? What was the status of the topic of (im)migration in the Polish public discourse before the so-called migration crisis? How has the image of the ‘other’ changed in the public debate of the last decades, years, months, and days? An attempt to answer these research questions requires a critical review of available research findings and relating them to previous and contemporary events. Current media reports of weekly opinion-forming magazines and daily newspapers (including online versions) provide comparative material. The main focus of attention is the way immigration and immigrants are written about (mainly nomination strategies, keywords, and metaphors). Referring to the available research results of the immigration discourse from years ago and comparing them with the current ones may indicate what we do “wrong” both “in” and “with” the aforementioned discourse and contribute to a more effective and substantive discussion of the phenomenon.